KONSEP TA’DĪB DALAM PEMBENTUKAN AKHLAK PESERTA DIDIK DI SMP NEGERI 3 SRAGI PEKALONGAN - Farokah, Umi; Muasomah (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
This research is motivated by the phenomenon of the decline of adab, such as the lack of courtesy of students to educators in behavior and in communication both inside and outside of learning. The concept of ta'dīb as the concept of educating is more focused on the process of forming morals. This study aims to determine the concept of ta'dīb in shaping students who have good morals. This research is a study that uses a qualitative approach, where the data is obtained through observation, interviews, and documentation. For data analysis techniques, researchers use three stages, namely through data reduction, data presentation, and conclusion drawing. The results of this study indicate that the concept of ta'dīb in shaping the morals of students at SMP Negeri 3 Sragi is through the exemplary method, habituation method, advice method, attention method, punishment method, and class confidence method. The supporting factors related to the concept of ta'dīb in shaping the morals of students at SMP Negeri 3 Sragi include the interest or awareness of each individual, the need for personal relationships between religious teachers and other teachers, the balance of relationships between family, school, and community environments. The inhibiting factors are the lack of awareness of the importance of education, especially moral education, the absence of collaboration between family, school and community environments, and the challenges of the times.